AN ETHICAL AND AN INTELLIGENT BUREAUCRATIC LAW REFORM - Jawade Hafidz (UNISSULA, 2020)
Bureaucracy and the law are two forces that must go hand in hand. Bureaucratic disregard the law when it goes limp bureaucratic system with no force because the bureaucratic system will not run when the law was abandoned. Bureaucracy in indonesia often look weak in a system. First rampant corruption in the bureaucracy is the main cause of dishonesty (actor) bureaucrats in understanding the nature of law. Breaking effects and misusing the mandate. Second, in our country as chaotic bureaucracy therein lies stagnation and the legal system in force when the bureaucracy that must be realized in accordance with the function and social role as a servant of the state. The third in the current law is enforced through a reformulation bureaucracy or bureaucratic reforms therein lies the role of bureaucracy is no longer comply with the law. Presence of bureaucracy in addition to be honest and transparent with the legal ethics bureaucracy is needed. Ethics is important in the bureaucracy. First, the existing problems in the bureaucracy becoming increasingly complex. Second, the success of development that has improved the dynamics and pace of change in the bureaucratic environment. Bureaucracy perform adjustment which requires discretionary power great.